2015
DOI: 10.1097/wnn.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cognitive Flexibility in Amyotrophic Lateral Sclerosis

Abstract: Objective Up to half of patients with amyotrophic lateral sclerosis (ALS) may have cognitive difficulty, but most cognitive measures are confounded by a motor component. Rare studies have related impaired cognition in ALS to disease in gray matter (GM) and white matter (WM). We evaluated a simple, untimed measure of executive functioning with minimal motor demands in ALS, and relate performance to structural disease. Methods Fifty-six patients with ALS and 29 matched healthy controls were assessed with the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…This area also has been associated with the strategic development of multistep planning such as that required to perform a task like the Tower of London ( Baker et al, 1996 ; Newman et al, 2003 ). Orbital frontal cortex has been associated with mental flexibility ( Milner, 1963 ; Kim and Ragozzino, 2005 ; Eslinger et al, 2007 ; Stalnaker et al, 2007 ; Evans et al, 2015 ), and disease in this area may be contributing to performance by limiting the ability to assess more than a limited range of possible quantitative estimates.…”
Section: Discussionmentioning
confidence: 99%
“…This area also has been associated with the strategic development of multistep planning such as that required to perform a task like the Tower of London ( Baker et al, 1996 ; Newman et al, 2003 ). Orbital frontal cortex has been associated with mental flexibility ( Milner, 1963 ; Kim and Ragozzino, 2005 ; Eslinger et al, 2007 ; Stalnaker et al, 2007 ; Evans et al, 2015 ), and disease in this area may be contributing to performance by limiting the ability to assess more than a limited range of possible quantitative estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of cognition in ALS have often focused on executive difficulty (1,46). However, a major confound for cognitive deficits is the motor disorder of ALS, and recent work has emphasized the identification of deficits that are independent of motor limitations (7,8). Deficits in language appear to occur at least as frequently as executive difficulty (5).…”
Section: Introductionmentioning
confidence: 99%
“…In confirmation of these results, we also found that our bvFTD subgroups, good and poor performers, were significantly different from one another in mental-set shifting, but not other EFs. Positive results may have been observed here because the visual-verbal test (Feldman and Drasgow, 1960) is particularly appropriate for use in clinical populations: it is brief, nonsocial, nonverbal, and has minimal motor demands (Eslinger et al, 2007; Evans et al, 2015). Other authors have found similar results concerning the role of mental set shifting in social behavior.…”
Section: Discussionmentioning
confidence: 64%